Development of Variable-Density Yield Models with Site Index Estimation for Korean Pines and Japanese Larch - Lee, Daesung; Choi, Jungkee (MDPI AG, 2022)
The objectives of this study were to develop site index and variable-density yield models for Korean red pine (Pinus densiflora Siebold & Zucc.), Korean white pine (P. koraiensis S. & Z.), and Japanese larch (Larix kaempferi (Lamb.) Carrière) in Korea. The data were collected between 2012 and 2021 from repeatedly measured empirical plots in each target stand in the North Central region of Korea: Gangwon and North Gyeongsang provinces. To develop the site index for each species, a dominant height growth model by species was developed using the Chapman–Richards function. The site index was computed with a base age of 40 years and used as an independent variable to predict the stand volume. To develop the variable-density yield models, three stand density variables, the stand age, and the site index were applied. The stand density variables used were the stand basal area, the number of trees per hectare, and the relative density. All the models were successfully developed with significant parameters and reasonable fit statistics, and the residuals analyzed presented unbiased scatter plots. Yield models with the stand basal area, or the number of trees, can be used to predict the stand volume. The yield model with relative density was flexible to apply across the stand age because the input of the absolute stand density was not required. Model simulation and comparisons with other studies also supported the applicability of the models developed in this study. The models were found to be highly applicable for predicting and simulating these targeted stands, particularly in Korea.
Keywords: Chapman–Richards function; mixed-effect models; stand volume; whole-stand models; relative density